Mendelian randomization analysis of CpG methylation and immune phenotypes in epithelial ovarian cancer outcomes - Jiawei Li; Wanjun Luo; Daohong Nie; Zidan Lin; Chenfei Zhou (Epigenetics)
Epithelial ovarian cancer (EOC) is a heterogeneous malignancy with distinct histological subtypes, and DNA methylation has emerged as a promising biomarker for early detection. However, the role of methylation patterns in EOC heterogeneity and prognosis remains unclear. In this study, genome-wide association studies (GWAS) data from the Ovarian Cancer Association Consortium (OCAC) and Methylation quantitative trait loci (mQTL) data from the Genetics of DNA Methylation Consortium (GoDMC) were analysed using two-sample Mendelian randomization (MR). We investigated the genetic effects of CpG methylation on the risk and prognosis of five major EOC histotypes. To further explore the mechanisms by which DNA methylation affects EOC outcomes, we performed mediation analysis to evaluate the role of immunophenotypes. Our analysis identified 94 CpG sites associated with high-grade serous ovarian cancer (HGSOC), 9 of which were linked to prognosis. Additional significant associations were found for clear cell, low-grade serous, endometrioid, and mucinous subtypes. Hypomethylation at specific CpG sites was linked to increased EOC risk and shorter survival. Mediation analysis revealed significant interactions between CpG methylation and immunophenotypes, suggesting that immune modulation mediates the effects of DNA methylation on EOC outcomes. These results provide novel insights into the importance of epigenetic and immune-related factors in EOC pathogenesis.